Evaluating the Benefits of a Computer Based Telecommunication Network: Telementoring and Teletraining for Educators in Rural Areas - Robbie M. Kendall (Journal of Research in Rural Education, 1991)
Telecommunication advances in computer based networking are fast becoming a vital information tool and resource in the field of education. The evaluation of the educational benefits oftelecommunications includes the delivery ofresources and training to educators in rural schools and the enhancement ofcommunication between educators andstudents. The evaluation ofthe Winthrop College Telementoring- Teletraining-Telecommunication Project has national and international implications.